Evaluasi Kompetensi Pengajar Matrikulasi Universitas Tribuana Kalabahi Tahun 2023 - Molebila, Eunike; Selly, Alboin; Bekata, Halena Muna; Malese, Lasarus Pelipus; Kafelkay, Seprianus (LPPM Institut Pendidikan Nusantara Global, 2024)
This evaluation research aims to evaluate the competence of matriculation teachers at Tribuana Kalabahi University which is based on student assessments to assess the competence of matriculation teachers in carrying out the learning process in the classroom which includes pedagogical competence, professional competence, personality competence and social competence. This evaluation activity is a routine activity carried out by LPM with the aim of ensuring that learning activities carried out by matriculation teachers have been carried out in accordance with the plans, objectives and standards or targets that have been set. This study uses a type of evaluation research with a quantitative approach using a survey method. The population in this study is 502 new students who took part in matriculation activities spread across 11 study programs at Tribuana Kalabahi University with data collection techniques using an online questionnaire. The data analysis technique uses descriptive statistics with percentage calculation techniques. The evaluation results show that in general the competency of matriculation lecturers can be concluded that the overall perception of respondents towards the 28 matriculation lecturers received a positive response with an average percentage score of 82.29% or in the High category. Pedagogical competence 81.14%, professional competence 82.55%, personality competence 83.80% and social competence 83.65%.